The road to more sustainable firms in the face of a pandemic: Changes needed in employment relationships. Issue 3 (July 2021) - Lopez-Cabrales, Alvaro; DeNisi, Angelo
The COVID-19 pandemic has changed the way we operate at work. Dealing with these changes may require new ways of thinking about our models of employment relationships, to create more sustainable organizations during troubled times. Sustainability can be understood as an attempt to strike a balance between the economic, social and environmental goals of companies—a balance that could drive a global recovery from the pandemic crisis. This essay focuses on the employer's perspective and considers how firms can use different employment models to improve sustainability during the crisis. We propose two alternative employment models which we label "Oversustainability" and "Mutual Sustainability" that depend on the choice of the firm's competitive strategy (proactive/innovative vs analyzer/following). We considered the contributions expected from employees and the inducements they were offered under each model. We believe these employment models can be advantageous for companies seeking to adopt proactive and analyzer-type sustainability strategies. JEL CLASSIFICATION M1